Pemahaman Konseptual Matematika dengan Model Discovery Learning terhadap Kemandirian Belajar Mahasiswa - Merina Pratiwi; Amiroel Oemara Syarief (Departement of Mathematics Education, 2023)
The learning process is still centered on lecturers so that achievements in understanding the concept are not optimal. Students are not used to independently finding concepts because they must always be guided by lecturers. Therefore, as an implication for conceptual understanding in mathematics, students must be able to learn independently through experiential learning in understanding concepts through Discovery Learning learning. To fulfill the conceptual understanding of mathematics, an independent learning with the Discovery Learning model is needed on the basis of self-motivation to carry out learning activities in solving problems. The purpose of this study is to determine the influence of conceptual understanding of mathematics with the Discovery Learning model on student learning independence. The method in this study is quantitative descriptive research using an ex post facto approach. Data collection techniques use mathematical conceptual comprehension tests and student learning independence questionnaires. Data processing techniques using linear regression tests. The results showed that student learning independence in learning with the Discovery Learning model did not affect students' conceptual understanding of mathematics.